The role of green roofs on atmospheric carbon removal in the neotropics. A revision (REVISTA NODO, 2012)
With the purpose of further determining the impact of green roofs on removing atmospheric CO2 the following is a thorough revision of scientific publications related to the issue. More than fifty documents were found, the greater part from North America and Asia as main contributors to this field of knowledge. The majority of them relate to thermal outcomes of green roofs on buildings, a lesser percentage deal with analyzing urban/environmental benefits of green roofs, and just a few discuss CO2 absorption capacity of green roofs based on already-published information. Thenceforth the mentioned revision, the intention is to fill in the gaps with studies about the role of green roofs in neotropical cities, as well as researches aimed to evaluate carbon retention on that specific type of roofing.
Keywords: Green building envelopes; CO2 removal; carbon retention